2021
DOI: 10.54300/987.779
|View full text |Cite
|
Sign up to set email alerts
|

California Teachers and COVID-19: How the Pandemic Is Impacting the Teacher Workforce

Abstract: California will need a stable, high-quality teacher workforce to weather the COVID-19 crisis and support student learning in the coming years. However, persistent and worsening teacher shortages threaten the state's ability to meet that need. Teacher shortages, which are often most acute in high-need fields and high-need schools, more severely impact students from low-income families and students of color, with significant implications for school stability and student achievement. Early evidence suggests that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 10 publications
2
39
0
Order By: Relevance
“…Teachers have been facing numerous challenges since the start of the pandemic, but limited attention has been placed on their professional well-being. A report interviewed superintendents and administrators from 17 California school districts (Carver-Thomas et al, 2021) in which the school leaders commonly expressed major concerns on teacher mental health and workload and worsening teacher shortage in the COVID-19 context. Likewise, available studies from other countries indicated deteriorating psychological health among teachers during the pandemic (e.g., Allen et al, 2020; Kim et al, 2020).…”
Section: Teacher Well-being During Covid-19mentioning
confidence: 99%
See 4 more Smart Citations
“…Teachers have been facing numerous challenges since the start of the pandemic, but limited attention has been placed on their professional well-being. A report interviewed superintendents and administrators from 17 California school districts (Carver-Thomas et al, 2021) in which the school leaders commonly expressed major concerns on teacher mental health and workload and worsening teacher shortage in the COVID-19 context. Likewise, available studies from other countries indicated deteriorating psychological health among teachers during the pandemic (e.g., Allen et al, 2020; Kim et al, 2020).…”
Section: Teacher Well-being During Covid-19mentioning
confidence: 99%
“…Job characteristics of the teaching profession have changed considerably in the face of the pandemic, especially with the swift transition from face-to-face to remote instruction (Carver-Thomas et al, 2021; Daniel, 2020). The Job Demand–Resource (JD–R) model proposes that employee well-being is affected by two types of job characteristics: job demands and job resources (Bakker & Demerouti, 2017).…”
Section: Teacher Well-being During Covid-19mentioning
confidence: 99%
See 3 more Smart Citations